2017
DOI: 10.7763/ijet.2017.v9.987
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drilled Cuttings Lifting Using Polypropylene Beads in Water-Based Mud at Different Annular Mud Velocities

Abstract: An effective drilled cuttings lifting from the bottomhole to the surface improves drilling performance. The transportation of drilled cuttings becomes more challenging when drilling a high angle or horizontal well. A sufficiently high annular mud velocity is essential to prevent drilled cuttings from settling and forming stationary beds on the low side of a hole. This can cause several drilling problems such as high torque and drag, stuck pipe, etc. This problem has been addressed via an experimental work whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 2 publications
3
11
0
Order By: Relevance
“…It could be observed that 45° holeangle inclination recorded the lowest CTE, indicating that it is the most challenging hole-angle for cuttings transportation. This behaviour could be ascribed to the tendency of The result obtained in the hole-angles of this study is in agreement with published reports of the following authors (Oseh et al 2018;Ismail et al 2016;Onuoha et al 2015;Ford et al 1990;Piroozian et al 2012;Ozbayoglu et al 2010;Sifferman and Becker 1992). They reported that cuttings transportation is more challenging in highly deviated and horizontal wells drilling than in straight hole-angle.…”
Section: Effects Of Hole-angles On Cuttings Transport Efficiencysupporting
confidence: 92%
See 4 more Smart Citations
“…It could be observed that 45° holeangle inclination recorded the lowest CTE, indicating that it is the most challenging hole-angle for cuttings transportation. This behaviour could be ascribed to the tendency of The result obtained in the hole-angles of this study is in agreement with published reports of the following authors (Oseh et al 2018;Ismail et al 2016;Onuoha et al 2015;Ford et al 1990;Piroozian et al 2012;Ozbayoglu et al 2010;Sifferman and Becker 1992). They reported that cuttings transportation is more challenging in highly deviated and horizontal wells drilling than in straight hole-angle.…”
Section: Effects Of Hole-angles On Cuttings Transport Efficiencysupporting
confidence: 92%
“…Decreased fluid velocity at the low side of the wall have been reported in numerous literatures to be the main cause of poor cuttings transportation with increasing hole-angle (Duan et al 2008;Ismail et al 2016;Ford et al 1990;Gavignet and Sobey 1989;Onuoha et al 2015). Gbadamosi et al (2018b), Hakim et al (2018), Elochukwu et al (2017), Afolabi et al (2017), Ismail et al (2016) and Piroozian et al (2012) all reported that the rheological and filtration properties of drilling fluids have significant contributions in determining the effectiveness of cuttings transportation. The rheological properties are often optimized to ensure that drilling fluid can function effectively and yet lessen the drilling cost.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations